Novel Targets in the Immune Microenvironment of the Hepatic Sinusoids for Treating Liver Diseases - Patten, Daniel A.; Shepherd, Emma L.; Weston, Christopher J.; Shetty, Shishir (Seminars in Liver Disease, 2019)
Immune dysregulation and accumulation of leukocytes is a hallmark of adult chronic liver diseases. Progressive hepatic inflammation can lead to fibrosis and cirrhosis with a high risk of liver failure or hepatocellular cancer (HCC). Recent advances have been made in the treatment of liver disease including the development of highly effective antiviral therapy for hepatitis C and the potential of immunotherapy for HCC. Despite this, the majority of other chronic liver diseases including alcoholic liver disease, fatty liver disease, and cholestatic diseases do not respond to conventional anti-inflammatory therapies. Recent studies defining the organ-specific properties that contribute to resident immune activation and immune cell recruitment from the circulation in these conditions have identified novel hepatic inflammatory pathways, which are now being targeted in clinical trials. Further understanding of how the immune microenvironment is regulated within the liver and how disease-specific mechanisms alter this process will hopefully lead to combination therapies to prevent aberrant inflammation and also promote fibrosis resolution. In this review, we focus on the advances that have been made in identifying key components of the inflammatory pathway including the recognition of danger signals, the recruitment and retention of lymphocytes from the circulation, and the pathways that promote resolution.
Keywords: Kupffer cells; liver sinusoidal endothelial cells; fibrosis; chronic inflammation